DAMPAK KEPUASAN KERJA DAN BEBAN KERJA TERHADAP KINERJA GURU: STUDI KUANTITATIF DI DAYAH HARAPAN UMMAT SIMPANG MAMPLAM BIREUEN - Ariska, Emalia; Mulyadi, Mulyadi; Zalikha, Zalikha; Yusuf, M.; Muchsin, Muchsin (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Performance can generally be defined as the work results or work achievements of an individual or a group of people in carrying out their duties and responsibilities within an organization or a specific time period. This research aims to analyze the influence of job satisfaction and workload on teacher performance at Dayah Harapan Ummat Simpang Mamplam Bireuen. The research method used is quantitative with a census sampling approach, involving 58 teachers as respondents. Data were collected through questionnaires with a Likert scale of 1-5. The data analysis technique used Multiple Linear Regression and was analyzed using SPSS 24 software. The research results show that job satisfaction and workload significantly influence teacher performance. Job satisfaction, reflecting teacher utility, is positively correlated with performance, indicating increased productivity. Managed workload, as a production factor, also positively influences performance, emphasizing efficient allocation of human resources. Simultaneously, both variables explain 78.3% of the variance in teacher performance, demonstrating a significant contribution to the effectiveness of educational organizations. The implications of this research are strategic human resource management in the education sector, focusing on improving job satisfaction and optimizing workload for superior organizational performance. This research provides empirical insights for the development of policies to enhance the quality of education through improved teacher welfare and productivity.